Current and Emerging Pharmacotherapeutic Interventions for the Treatment of Peripheral Nerve Disorders - Jeremy Chung Bo Chiang; Ria Arnold; Roshan Dhanapalaratnam; Maria Markoulli; Arun V. Krishnan (MDPI AG, 2022)
Peripheral nerve disorders are caused by a range of different aetiologies. The range of causes include metabolic conditions such as diabetes, obesity and chronic kidney disease. Diabetic neuropathy may be associated with severe weakness and the loss of sensation, leading to gangrene and amputation in advanced cases. Recent studies have indicated a high prevalence of neuropathy in patients with chronic kidney disease, also known as uraemic neuropathy. Immune-mediated neuropathies including Guillain-Barré syndrome and chronic inflammatory demyelinating polyradiculoneuropathy may cause significant physical disability. As survival rates continue to improve in cancer, the prevalence of treatment complications, such as chemotherapy-induced peripheral neuropathy, has also increased in treated patients and survivors. Notably, peripheral neuropathy associated with these conditions may be chronic and long-lasting, drastically affecting the quality of life of affected individuals, and leading to a large socioeconomic burden. This review article explores some of the major emerging clinical and experimental therapeutic agents that have been investigated for the treatment of peripheral neuropathy due to metabolic, toxic and immune aetiologies.